(untitled) (Research, Society and Development, 2020)
Dietary intake involves complex interactions between nutrients and non-nutrients. Moreover, dietary components can influence gene activity and influence human health, because they are directly related to DNA synthesis and maintenance. DNA integrity and stability are essential for life, while, DNA damage contributes mainly to disease development. The present study aimed to review the literature about the influence of dietary factors and the presence of DNA damage through the comet assay in the last decade. The literature review was performed using PubMed, LILACS and Scielo databases, with the terms "comet assay", "diet" and "dietetic" in Portuguese and English. The review identified 647 studies, after applying the inclusion and exclusion criteria, 28 articles were included in the review. It was observed high methodological quality in the included studies and a few studies that evaluated the dietary pattern and DNA damage. In general, fruit and vegetable intake and dietary supplementation or multivitamin compounds had higher positive impact on DNA damage.